Synthesis and in vitro Biological Studies of Copper Complexes Derived from Some Novel Hetero-Organoselanylquinoline Ligands - Moohambihai, P.; Nagashri, K. (Journal of Scientific Research, 2022)
A set of copper(II) complexes (3a-i) comprises (16E)-N-(2-phenylquinolin-4(1H)-ylidene)-3-(phenlselanyl)pyridine-2-amine (L1-L3), (16E)-2,6-dimethyl-N-(2-phenylquinolin-4(1H)-ylidene)-5-(phenlselanyl)pyrimidine-4-amine (L4-L6), 16E)-N-(2-phenylquinolin-4(1H)-ylidene)-2-(phenylselanyl)H-imidazo[1,2-α]pyridine-3-amine (L7-L9) ligands were synthesised and characterised using spectroscopic techniques. The metal-to-ligand 1:1 stoichiometry of prepared copper complexes was confirmed by mass spectra. The Cu(II) ion produces complexes with a distorted square planar, according to UV–Vis and ESR spectroscopy studies. The antioxidant activity of these complexes has been determined. The cytotoxic potential of the complexes was also investigated in vitro. The complex 3f was found to have significant cytotoxicity against MCF-7. The DNA binding characteristics of copper(II) complexes were investigated. The findings indicate that the complexes interacted with the calf thymus (CT-DNA). In addition, the complexes were tested in vitro for antimicrobial activity against three Gram-negative bacteria, three Gram-positive bacteria, and three Fungi.